Can texture analysis in ultrashort echo‐time MRI distinguish primary graft dysfunction from acute rejection in lung transplants? A multidimensional assessment in a mouse model. Issue 1 (31st May 2019) - Euler, André; Blüthgen, Christian; Wurnig, Moritz C.; Jungraithmayr, Wolfgang; Boss, Andreas
Abstract : Background: Differentiation of early postoperative complications affects treatment options after lung transplantation. Purpose: To assess if texture analysis in ultrashort echo‐time (UTE) MRI allows distinction of primary graft dysfunction (PGD) from acute transplant rejection (ATR) in a mouse lung transplant model. Study Type: Longitudinal. Animal Model: Single left lung transplantation was performed in two cohorts of six mice (strain C57BL/6) receiving six syngeneic (strain C57BL/6) and six allogeneic lung transplants (strain BALB/c (H‐2K d )). Field Strength/Sequence: 4.7T small‐animal MRI/eight different UTE sequences (echo times: 50–5000 μs) at three different postoperative timepoints (1, 3, and 7 days after transplantation). Assessment: Nineteen different first‐ and higher‐order texture features were computed on multiple axial slices for each combination of UTE and timepoint (24 setups) in each mouse. Texture features were compared for transplanted (graft) and contralateral native lungs between and within syngeneic and allogeneic cohorts. Histopathology served as a reference. Statistical Tests: Nonparametric tests and correlation matrix analysis were used. Results: Pathology revealed PGD in the syngeneic and ATR in the allogeneic cohort. Skewness and low‐gray‐level run‐length features were significantly different between PGD and ATR for all investigated setups ( P < 0.03). These features were significantly different between graft and native lung in ATR for most setups (minimum of 20/24 setups; all P < 0.05). The number of significantly different features between PGD and ATR increased with elapsing postoperative time. Differences in significant features were highest for an echo‐time of 1500 μs. Data Conclusion: Our findings suggest that texture analysis in UTE‐MRI might be a tool for the differentiation of PGD and ATR in the early postoperative phase after lung transplantation. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2020;51:108–116.